An evaluation of Kd-Trees vs Bounding Volume Hierarchy (BVH) acceleration structures in modern CPU architectures - Ernesto Rivera-Alvarado; Julio Zamora-Madrigal (Tecnología en Marcha)
Ray tracing is a rendering technique that is highly praised for its realism and image quality. Nonetheless, this is a computationally intensive task that is slow compared to other rendering techniques like rasterization. Bounding Volume Hierarchy (BVH) is a primitive subdivision acceleration mechanism that is the mainly used method for accelerating ray tracing in modern solutions. It is regarded as having better performance against other acceleration methods. Another well-known technique is Kd-Trees that uses binary space partitioning to adaptively subdivide space with planes. In this research, we made an up-to-date evaluation of both acceleration structures, using state-of-the-art BVH and Kd-Trees algorithms implemented in C, and found out that the Kd-Trees acceleration structure provided better performance in all defined scenarios on a modern x86 CPU architecture.